Optimal routing and heterogeneous resource allocation for computing-aware networks - Ding, Hongqing; He, Fujun; Zhang, Pengfei; Zhang, Liang; Zhang, Xiaoxiao; Qi, Meiyu (ICT express, 2024)
Computing-aware networking (CAN) is introduced to unite the computing resources distributed in different platforms. This paper proposes a joint routing and resource allocation model to minimize the total operational cost in CAN. We formulate the problem as an integer linear programming problem. We introduce a polynomial-time algorithm for larger-size problems. The numerical results reveal that the introduced algorithm reduces the computation time 9.18 times, with increasing the objective no more than 4% compared to the optimal solution; the proposed model can reduce 70% of the total cost compared to a baseline adopting a two-stage strategy in our examined cases.